Application of Breast Care to Prevent Breast Milk Dams in Postpartum Mothers - Fitriani Agustina; Handry Darussalam; Indah Julia (Lentera Perawat, 2024)
The first day after delivery is when the breasts become overfilled with milk, causing them to become swollen, hard and painful. Breast care is an action to take care of the breasts to prevent the occurrence of breast milk dams, reduce pain and discomfort, prevent more serious complications, maintain breast milk production, prevent early termination of breastfeeding breast milk. The purpose of this case study is to provide nursing care to post partum mothers with the problem of ineffective breastfeeding with the application of Breast Care.  The research method used is a case study of 2 patients with post partum by applying the nursing process method: Interview, examination, observation of activities to obtain diagnostic records and reports. After taking nursing action for 3 days with a diagnosis: ineffectiveness of breastfeeding associated with breast swelling. with the application of breast care with the results resolved on day 4. breast discomfort has decreased after breast care, there is no dam or swelling in the mother's breast, there is no dam or swelling in the mother's breast, feeling more relieved and relaxed after breast care is performed. The application of breast care in both post partum patients can reduce breast swelling due to breast milk dams. Researchers suggest that patients can apply breast care as one of the treatments that can be done alone at home, because one of the benefits of breast care is to reduce breast swelling.